Good cancer follow-up for socially disadvantaged patients in general practice? Perspectives from patients and general practitioners - Lotte Lykke Larsen; Camilla Hoffmann Merrild (Scandinavian Journal of Primary Health Care, 2024)
AbstractOne of the core principles of providing care in general practice is giving more to those who need it most. We investigate some of the complexities of this ambition in the context of cancer care for patients defined as socially disadvantaged by their general practitioner (GP). We do this by exploring how care is sought, how it is offered, and what expectations patients and GPs carry with them when receiving and providing cancer care in the Danish welfare state. We carried out semi-structured interviews with eight GPs and seven socially disadvantaged cancer patients living with different types and stages of cancer. The interviews focused on needs and challenges in cancer follow-up in general practice and were thematically coded. Drawing on theoretical concepts of morality and Nordic individualism, we point to how one of the main challenges in cancer care and follow-up is to figure out how the doctor-patient relationship should be established, practiced, and maintained. Both GPs and patients stressed the importance of the relationship, but how it should be practiced amidst social norms about being a patient, a citizen and how care-seeking should unfold seems less clear. In conclusion we argue that giving more to those who need it the most is a difficult and ill-defined task that is shaped by the cultural, social, and political expectations of both GPs and patients.